1999
DOI: 10.1021/bi9827971
|View full text |Cite
|
Sign up to set email alerts
|

Sliding Clamp of the Bacteriophage T4 Polymerase Has Open and Closed Subunit Interfaces in Solution

Abstract: The sliding clamps of bacteriophage T4 (gp45), Escherichia coli (beta clamp), and yeast (PCNA) are required for processive DNA synthesis by their cognate DNA polymerases. The X-ray crystal structures of all three of these clamps have been shown to be closed, circular complexes. This paper reports investigations of the solution structure of bacteriophage T4 gp45 by analytical ultracentrifugation, fluorescence, and hydrodynamic modeling. Mutants of gp45 with inter- and intrasubunit disulfide bonds were created t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
117
0
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(128 citation statements)
references
References 42 publications
10
117
0
1
Order By: Relevance
“…Oligonucleotide primers and substrates were prepared as previously described (14,33,34). The forked bio62͞34͞36mer primer-template blocked with streptavidin (34) was used as the DNA substrate in all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Oligonucleotide primers and substrates were prepared as previously described (14,33,34). The forked bio62͞34͞36mer primer-template blocked with streptavidin (34) was used as the DNA substrate in all experiments.…”
Section: Methodsmentioning
confidence: 99%
“…pET26b-W92F͞S158C͞W199F and pET26b-W92F͞ T168C͞W199F were then created from the respective mutants above by using fragments AH and BG in the overlap extension reaction yielding a new BsiEI site. Purification and labeling with CPM were performed as described previously (12,33). Mutations were confirmed by DNA sequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The polymerase C-terminal region was shown to interact with the interdomain loop of one of the clamp subunits. However, solution studies revealed a clamp structure with one open and two closed interfaces (20) and strongly argued for an interaction between the polymerase C terminus and the open clamp subunit interface (21,22). The x-ray data and its associated holoenzyme model which used the weaker interdomain binding site of gp45 was predicted, however, to play some role in holoenzyme assembly, DNA replication, translesion bypass, or other replication associated processes (19,21).…”
Section: The Effect Of Trap Concentration At Constant Wt͞trap Polymerasementioning
confidence: 99%
“…That the clamp bound to the clamp loader is in a closed form in the crystal structure of the RFC-PCNA complex came as a surprise, because the engagement of an ATP-bound clamp loader with the clamp is known to result in clamp opening (15,19,20). The crystal structure may correspond to a state of the system just before the release of the clamp on DNA.…”
mentioning
confidence: 99%